2012
DOI: 10.1177/1747016112445420
|View full text |Cite
|
Sign up to set email alerts
|

Ethical and safe: Research with children about domestic violence

Abstract: Ethics applications to conduct research with children who have experienced domestic violence will frequently raise a red flag to ethics committees about the potential for risk and retraumatization. On the other hand, such sensitive research can enable a hidden, marginalized population to have their voices heard. It can deliver findings about children's lives that can inform otherwise adult-centric research, policy and practice initiatives. The authors highlight ethical concerns and practical solutions using ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
90
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 36 publications
0
90
0
Order By: Relevance
“…As researchers we were mindful of the way that children were positioned as vulnerable and negatively impacted by their experiences of domestic violence: asking children to articulate their experiences might be risky or subject them to secondary traumatisation (Eriksson & Näsman, 2012;Morris, Hegarty, & Humphreys, 2012), but we were also committed to facilitating their ability to articulate and make meaning of their own experiences (Houghton, 2015;Skansvors, 2009). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As researchers we were mindful of the way that children were positioned as vulnerable and negatively impacted by their experiences of domestic violence: asking children to articulate their experiences might be risky or subject them to secondary traumatisation (Eriksson & Näsman, 2012;Morris, Hegarty, & Humphreys, 2012), but we were also committed to facilitating their ability to articulate and make meaning of their own experiences (Houghton, 2015;Skansvors, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Children were only interviewed if they had left situations of domestic abuse, and if professionals working with them assessed them to be safe to work with (Morris et al, 2012). If children were distressed, or if the researchers had concerns about their wellbeing, specialist domestic violence workers were accessible for consultation and if necessary, immediate referral.…”
Section: Methodsmentioning
confidence: 99%
“…The research was ethically complex, as we managed the tension between children's right to articulate their experiences (Cater & Øverlien, 2014;Houghton, 2015), the need to be sensitive to the potential distress involved in talking to children about their experiences, as well as the risk of violent reprisals (Eriksson & Näsman, 2012;Morris, Hegarty, & Humphreys, 2012). We supported children to find safe ways to tell their own stories, respecting their capacity to make sense of their own experiences (Alderson creative techniques like photo and graphic elicitation (Fargas-Malet, McSherry, Larkin, & Robinson, 2010).…”
Section: Ethicsmentioning
confidence: 99%
“…We supported children to find safe ways to tell their own stories, respecting their capacity to make sense of their own experiences (Alderson creative techniques like photo and graphic elicitation (Fargas-Malet, McSherry, Larkin, & Robinson, 2010). Children were only interviewed if they had left situations of domestic violence, or if professionals working with them had assessed them to be safe to work with (Morris et al, 2012). Researchers had clear safety protocols and received guidance and ongoing support from mental health workers and DV specialists, whom they could contact to facilitate additional support for families, or make referrals if they had concerns about children.…”
Section: Ethicsmentioning
confidence: 99%
“…In this way, children are understood to be active agents in their own lives and ongoing efforts are needed to ensure that children's views are taken seriously and that their rights to be heard are being upheld (O'Kane, 2017). While research with children in the context of family violence often focuses on the risks and potential dangers of their involvement, authors such as Överlien (2010) and Morris, Hegarty, and Humphreys (2012) have advocated for equal emphasis to be placed on the opportunities for collaborating with children and highlighted the potential positive outcomes in children's lives as well as for the broader community as a result of their involvement. Lundy and colleagues (2011) have advocated for an approach that values children as experts in their own lives and suggested that involving children in the representation of research ensures that new knowledge is grounded in the perspective of children themselves, rather than adults providing interpretations of children's experiences.…”
Section: Ethical Considerationsmentioning
confidence: 99%